The 18th Constitutional Amendment and Provincial Autonomy in Pakistan: A Critical Analysis of Federalism and Decentralization - Khurram Shahzad; Dr. Shahid Rizwan; Dr. Shahida Naz (Dialogue Social Science Review (DSSR), 2025)
The 18th Constitutional Amendment, adopted in 2010, became one of the milestones of the constitutional and political development of Pakistan. Its purpose was to transform the federal order by transferring important legislative and administrative prerogative to the provinces. The amendment would help achieve old unanswered demands of provincial autonomy and province wise fair governance by ending periodic pressure on the termination of the Concurrent Legislative List and growing the role of the Council of Common Interests (CCI). There has been recognition among scholars of its symbolic and structural value; only little empirical work has been done on assessing its actual effects on federal-provincial relations and administrative performance. This paper attempts to critically analyze how much the 18 th amendment has redefined federalism in Pakistan and led to substantive decentralization. The article employs a doctrinal approach to legal research that considers the constitutional text, judicial interpretations, legislative history and scholarly materials. This study points out a discrepancy between the theoretical potential of the amendment and its practical application that indicates that despite the changes in the constitutional parameters, the weaknesses of the institutions, intergovernmental tensions, and variances in the administration still act as a hindrance to the efficacy of the constitutional framework. The research adds to the overall discourse about federalism in growing democracies and indicates that more coordination practices, more pronounced division of duties, and capacity-building actions on provincial governance are needed (Shah, 2012; Ahmed, 2020).